Case report: Delayed cardiac rupture with congenital absence of pericardium after blunt trauma - Shen, Tuo; Fang, He; Tang, Tao; Tang, Hongtai; Hu, Xiaoyan; Zhu, Feng (Frontiers in Cardiovascular Medicine, 2022)
A 66 years old male was admitted to our hospital after a serious car accident. The patient presented with severe shock after admission. After the examination, the patient was diagnosed with hemopneumothorax and myocardial contusion, accompanied by spleen rupture. After emergency surgery and a series of symptomatic treatments, the patient’s condition gradually stabilized. One week later, the patient suddenly presented with severe shock. Massive hemothorax was found on the left side of the chest. Surgical exploration revealed cardiac rupture and accidental absence of congenital pericardium. According to the literature review, congenital absence of pericardium (CAP) is relatively rare. Although there are certain imaging features, the clinical diagnosis is very difficult. However, this patient did not show the characteristics in the literature and had some other atypical features. The role of CAP in the occurrence and development of the patient’s heart injury and rupture is worthy of discussion. What we learned from this case is that we should look for potential risks in the telltale signs of a patient’s condition.